Avaliação do desempenho de concretos refratários ao ataque por escória de redução de chumbo secundário em forno rotativo. - Prestes, Eduardo (2007)
The recycled lead obtained mainly from the recovery of lead from lead-acid batteries is named secondary lead. The process of lead scrap smelting and reduction is carried out in short rotary furnaces and the standard refractory lining is the burned magnesia-chromite bricks. The employment of refractory castables is not found in the literature for this type of application. Therefore, this research provides an evaluation by slag attack of commercial castable refractories selected for short rotary furnace application of secondary lead smelting in confrontation with commercial burned magnesia-chromite bricks. After the scorification tests, statics and dynamics, the wear and slag penetration area in each sample was measured using the analysis image software “Image- Pro Plus 5.1”. For the best performance products was realized the corrosion study by analysis of the refractory-slag interface by Scanning Electronic Microscopy (SEM), Energy Dispersive Scanning (EDS) and X-Ray Diffractometry. Sintered magnesia-chrome spinel bricks showed the best slag attack resistance and the evaluated castable refractories showed inferior performance than the standards refractory bricks. Nevertheless, a low cement alumina-chrome castable based on white fused alumina was similar to performance of the direct bonded magnesia-chromite bricks. This result shows that the employment of castable refractory in short rotary furnace of secondary lead smelting is very promising. The analysis of the refractory products after the static and dynamic slag attack showed that the FeO is the main corrosive agent of the slag, due to its reaction with components of refractory and formation of low melting compounds.